The effect of educational workshop on emergency department nurses' self-efficacy in patient training - Hojjat Sheikhbardsiri; Syed Hossein Mousavi; Mohammad Mahdi Doustmohammadi; Masoumeh Karimi; Sahar Salahi (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVE: Self-efficacy is an individual's self-perception of one's ability to perform competently and to achieve a task or goal effectively. In the nursing field, self-efficacy can be useful in predicting performance, job satisfaction, or well-being. Therefore, due to the importance of this issue, this study aimed to determine the effect of educational workshop on nurses' self-efficacy along with follow-up in patient training. METHODS: The study employed a single group quasi-experimental study with a pretest/posttest design and was conducted in one educational hospital supervised by the Kerman University of Medical Sciences in 2016. Nurses' self-efficacy was analyzed through a researcher-made questionnaire prior and after the workshop and along with the follow-up period (n = 20). Data were analyzed using descriptive statistics including mean and standard deviation and analytic statistics such as Pearson correlation coefficient, independent t-test, paired t-test, and ANOVA with P ≤ 0.05. RESULTS: This study showed that 1 month after educational workshop, the score of self-efficacy dimensions increased (P < 0.05). Furthermore, results showed that after a 3-month follow-up period, self-efficacy score increased in comparison to preintervention self-efficacy score. Results showed that the total score means of self-efficacy before the workshop was 59.01 ± 14.91 while postworkshop, self-efficacy score means was 79.83 ± 11.90. CONCLUSION: The present research results presented that educational workshop may enhance self-efficacy among nurses. According to the obtained results, it is recommended that the Ministry of Health, Treatment and Medical Training, in cooperation with nursing institutions responsible for nursing and medical in-service education adopt necessary measures to enhance self-efficacy among employees in addition to improving patient training condition at medical processes through similar workshops or conducting related studies.